KOMPETENSI PENDIDIK DALAM MENGHADAPI TANTANGAN PEMBELAJARAN PAI PADA MASA BELAJAR DARI RUMAH - Laili Masudah (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
PAI learning is not only transferring science but also transforming the values of The Law more comprehensively in an interesting and challenging way so that students are able to explore all the potentials they have and steer towards postiif. In times of pandemic according to government policies that require learning from home, students encounter some challenges when attending lessons. The challenge must be eroded so as not to become a barrier. Challenges are present both from within the students and the environment. The period of learning from home is new to all educational circles. Students will inevitably be asked to study independently and responsibly without direct guidance from the teacher. They are required to follow online learning. Educators who usually meet in real time with students, currently rely solely on communication or what is often called distance learning. Both material delivery, workmanship and assessment are all carried out in the network. Educators are also required to be more productive, creative and innovative in crafting each meeting in order to be developed into good opportunities. In order for all to be implemented, educators as learning drive motors are required to apply competencies that are able to answer the challenges. Competencies derived from the Qur'an and hadith of the Prophet are expected to be relevant and able to be the best solution that educators can apply in the study period from home.